2020
DOI: 10.3389/fmicb.2020.01950
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Abundance of Biosynthetic Gene Clusters in Shark Bay Microbial Mats

Abstract: Microbial mats are geobiological multilayered ecosystems that have significant evolutionary value in understanding the evolution of early life on Earth. Shark Bay, Australia has some of the best examples of modern microbial mats thriving under harsh conditions of high temperatures, salinity, desiccation, and ultraviolet (UV) radiation. Microorganisms living in extreme ecosystems are thought to potentially encode for secondary metabolites as a survival strategy. Many secondary metabolites are natural products e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 83 publications
1
61
0
Order By: Relevance
“…The study of extant stromatolite analogues may help to elucidate the biological mechanisms that led to the formation and evolution of their ancient ancestors. The biogenicity of stromatolites has been studied extensively in the hypersaline and marine formations of Shark Bay, Australia, and Exuma Cay, The Bahamas, respectively (Khodadad and Foster, 2012; Mobberley et al ., 2015; Centeno et al ., 2016; Gleeson et al ., 2016; Ruvindy et al ., 2016; Warden et al ., 2016; White et al ., 2016; Babilonia et al ., 2018; Wong et al ., 2018; Chen et al ., 2020). The presence of Archaea has been noted in several microbial mats and stromatolite systems (Casaburi et al ., 2016; Balci et al ., 2018; Medina‐Chávez et al ., 2019; Chen et al ., 2020), particularly in the stromatolites of Shark Bay, where they are hypothesized to potentially fulfil the role of nitrifiers and hydrogenotrophic methanogens (Wong et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of extant stromatolite analogues may help to elucidate the biological mechanisms that led to the formation and evolution of their ancient ancestors. The biogenicity of stromatolites has been studied extensively in the hypersaline and marine formations of Shark Bay, Australia, and Exuma Cay, The Bahamas, respectively (Khodadad and Foster, 2012; Mobberley et al ., 2015; Centeno et al ., 2016; Gleeson et al ., 2016; Ruvindy et al ., 2016; Warden et al ., 2016; White et al ., 2016; Babilonia et al ., 2018; Wong et al ., 2018; Chen et al ., 2020). The presence of Archaea has been noted in several microbial mats and stromatolite systems (Casaburi et al ., 2016; Balci et al ., 2018; Medina‐Chávez et al ., 2019; Chen et al ., 2020), particularly in the stromatolites of Shark Bay, where they are hypothesized to potentially fulfil the role of nitrifiers and hydrogenotrophic methanogens (Wong et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The biogenicity of stromatolites has been studied extensively in the hypersaline and marine formations of Shark Bay, Australia, and Exuma Cay, The Bahamas, respectively (Khodadad and Foster, 2012; Mobberley et al ., 2015; Centeno et al ., 2016; Gleeson et al ., 2016; Ruvindy et al ., 2016; Warden et al ., 2016; White et al ., 2016; Babilonia et al ., 2018; Wong et al ., 2018; Chen et al ., 2020). The presence of Archaea has been noted in several microbial mats and stromatolite systems (Casaburi et al ., 2016; Balci et al ., 2018; Medina‐Chávez et al ., 2019; Chen et al ., 2020), particularly in the stromatolites of Shark Bay, where they are hypothesized to potentially fulfil the role of nitrifiers and hydrogenotrophic methanogens (Wong et al ., 2017). Studies of freshwater microbialites in Mexico found that there were significantly more genes associated with phosphate uptake and metabolism than in other communities associated with fresh or marine waters (Breitbart et al ., 2009) and that nitrogen fixation by heterocystous cyanobacteria, sulfur‐reducing bacteria, and purple sulfur bacteria was important to the formation of these particular stromatolites (Falcón et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…25% in this survey. Previous short-read metagenomic studies of aquatic and soil environments also reported high numbers of terpene BGCs, with terpenes representing between 15% and 50% of the reported BGCs, respectively [57][58][59] . However, the representativeness of BGC counts obtained through metagenomic studies remains questionable.…”
Section: Discussionmentioning
confidence: 82%
“…In the ‘microbial mat’ environment microorganisms are exposed to high temperatures, UV radiation and salinity [157] , with a high diversity of NRPS and hybrid NRPS-PKS genes in bacteria of the phyla Planctomycetes, Chloroflexi, Calditrichaeota and for the first time Lokiarchaeota was reported. Lokiarchaeota is an archaeal phyla not previously known to have BGCs, expanding the domain of life to which the future of natural products discovery can take place [158] .…”
Section: Discovery Of New Lps: Where Are We Going?mentioning
confidence: 99%
“…Microorganisms thrive in a myriad of ‘extreme’ environments, from hot springs and geysers, through to deep sea, hypersaline environments, evaporites, deserts, cold environments (ice, permafrost, and snow) and the Earth’s atmosphere. Given the diversity of genetic machinery recently discovered in microorganisms from Antarctic deserts and microbial matts [140] , [158] , we believe future investigations in a range of ecosystems at the boundaries of life will provide new insights into the ecological roles of LPs [24] . We know that microorganisms exposed to harsh conditions develop biological adaptations, metabolic processes, physiological capabilities and novel strategies to survive, and remain metabolically active in their unique environments [24] .…”
Section: Discovery Of New Lps: Where Are We Going?mentioning
confidence: 99%